2008
DOI: 10.1080/07420520802387773
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Variation of Plasma Brain‐Derived Neurotrophic Factor (BDNF) in Humans: An Analysis of Sex Differences

Abstract: Scant information is available on the diurnal variation of peripheral neurotrophic factors, including brain-derived neurotrophic factor (BDNF), in human beings. We explored plasma and serum BDNF levels at three different clock times in a study of 28 healthy subjects of both sexes. Statistically significant diurnal variation in plasma BDNF level was detected in men, with the peak at 08:00 h and nadir at 22:00 h. At this time, the plasma BDNF concentration of men was significantly lower than that of women (p=.02… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
77
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(85 citation statements)
references
References 23 publications
7
77
1
Order By: Relevance
“…Because the storage time of the samples was no longer than 5 years and the subjects were fasting before the samples were taken, we did not expect any influence of these determinants on the BDNF levels in the present study. Diurnal variation has been reported for plasma BDNF levels, but not for serum BDNF levels [33], we also did not expect any influence of diurnal variation on the outcomes of the present study. Despite its limitations, as far as we know, this is the first study that evaluates serum BDNF and EGF levels in patients with schizophrenia with depression compared to not only a healthy control group but a schizophrenia and major depression group.…”
Section: Discussionsupporting
confidence: 55%
“…Because the storage time of the samples was no longer than 5 years and the subjects were fasting before the samples were taken, we did not expect any influence of these determinants on the BDNF levels in the present study. Diurnal variation has been reported for plasma BDNF levels, but not for serum BDNF levels [33], we also did not expect any influence of diurnal variation on the outcomes of the present study. Despite its limitations, as far as we know, this is the first study that evaluates serum BDNF and EGF levels in patients with schizophrenia with depression compared to not only a healthy control group but a schizophrenia and major depression group.…”
Section: Discussionsupporting
confidence: 55%
“…This apparent inconsistency may be explained by the altered platelet function of smokers (Winther and Fornitz, 1999) and the size of the sample that was studied. Platelets represent a major storage site for BDNF in the peripheral blood (Fujimura et al, 2002), while diurnal rhythm BDNF levels were found in plasma but not in serum (Piccinni et al, 2008). Plasma BDNF concentrations significantly decrease with increases in age or weight, whereas platelet or serum levels do not seem to change (Lommatzsch et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In healthy males, plasma BDNF follows a circadian rhythm, similarly to cortisol (191): peak in the morning (8:00) and nadir in the night with a minimum between 10:00 pm and midnight (191)(192)(193). Interestingly, this rhythm was significant only in plasma in men; diurnal variation was found neither in plasma BDNF of women, during the menstrual cycle, nor in serum BDNF level in both men and women (192).…”
Section: Pre-analytical Factorsmentioning
confidence: 94%